Development of tax control in the context of digitalization of the economy - L. V. Reunova; L. A. Mamiek; L. V. Prigoda; T. A. Paladova (Новые технологии)
Tax control is the main fiscal and regulatory tool of the modern economy, and digital technologies, in turn, are the main tool of tax control. The article considers the impact of digitalization processes occurring in the modern economy on tax control procedures. Modernization of tax processes is explained by the active use of the latest digital technologies in tax administration in the form of various tools in order to minimize tax risks from tax evasion of legal entities and individuals. As an example, a comparative analysis of the indicators of the control work of the Departments of the Federal Tax Service of Russia for the Republic of Adygea and the Krasnodar Territory for 2017-2019 has been carried out and conclusions drawn as to how the effectiveness of tax audits has changed in connection with the expansion of the informatization of the tax service. It has also been concluded that improving the efficiency of in-office inspections based on the introduction of new modern technologies can be called a promising direction of the control activity of the tax service, especially since in-office inspections are carried out permanently with almost complete quantitative coverage of all business entities. To make informed management decisions at different levels of management, a comprehensive comparative assessment of the effectiveness of the control work of tax authorities is necessary. In general, it has been noted that the development of digitalization has a positive impact on the effectiveness of tax control and allows moving away from conducting direct tax audits to creating incentives for taxpayers to voluntarily pay taxes and clarify their tax obligations. In addition, digitalization eliminates such a competitive advantage in the market as the tax component, and leads to more favorable conditions for the implementation of business activities and the growth of the state economy.